Governing open access: livestock distributions and institutional control in the Karakum Desert of Turkmenistan. (March 2016) - Behnke, Roy; Robinson, Sarah; Milner-Gulland, E.J.
Highlights: This paper describes a non-exclusive pastoral land use system in Turkmenistan. Livestock distributions mirrored resource distributions in the study area. The matching of livestock populations to resource concentrations implies open access. A land tenure system operated in the study area and governed herd movements. The land tenure system was not used to exclude outsiders but to regulate sharing. Tenure rights structured, legitimated and facilitated free livestock distributions Abstract: On the edge of the Karakum Desert in Turkmenistan, the distribution of livestock in space and time can with reasonable accuracy be interpreted in terms of the model of the ideal free distribution: The number of livestock supported by desert settlements varies with the level of resources in a settlement; the propensity of herds to migrate seasonally is a density-dependent function of grazing pressure; migratory cycles exploit temporal fluctuations in feed and water quality between regions. Ideal free models are premised on the assumption that resource consumers have unrestricted access to resources. In conventional economic analyses, open or unrestricted access is equivalent to the absence of land tenure. A formal tenure system, involving the state ownership of land and the management of state lands by collective farms, nonetheless operated in the study area, and was referred to by farm managers and by pastoralists when making decisions about herd movement and resource use. The operation of this tenure system was also demonstrated by the restrictions that it imposed on communities with insufficient resource entitlements. In the great majority of cases, however, and in terms of the land use system as a whole, the tenure system facilitated a process of orderly and free distribution of livestock relative to resources. This paper examines the reasons for and functioning of this theoretical oxymoron—a regulated system of open access. The study contributes to a growing body of literature on the non-exclusive nature of pastoral tenure systems in Africa and Asia.